(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Two ways of calculating the wear rate was investigated experimentally by weight and volume using aluminum samples with different load (500g, 1000g, and 1500g) and different time of test (300 s, 600 s, and 900 s). The results show that, When the load increasing from 500 g to 1500 g the wear rate by weight increase by (83%, 80%, and 37%) for test time (300s, 600s, and 900s) respectively. Also, the increasing test time from 300s to 900 s causes increasing in wear rate by weight by (216%, 155%, and 136%) for load (500g, 1000g, and 1500g) respectively. Also, when the load increasing from 500 g to 1500 g the wear rate by volume increase by (740%, 612%, and 662%) for test time (300s, 600s, and 900s) respectively. Also, the increasing test time from 300s to 900 s causes increasing in wear rate by volume by (152%, 110%, and 128%) for load (500 g, 1000g, and 1500g) respectively.